2020
DOI: 10.1016/j.ecoenv.2020.111069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paralytic shellfish toxins on the middle intestine of Oncorhynchus mykiss: Glutathione metabolism, oxidative status, lysosomal function and ATP-binding cassette class C (ABCC) proteins activity

Abstract: We studied the absorption, cytotoxicity and oxidative stress markers of Paralytic Shellfish Toxins (PST) from three extracts from Alexandrium catenella and A. ostenfeldii, in middle Oncorhynchus mykiss intestine in vitro and ex vivo preparations. We measured glutathione (GSH) content, glutathione-S transferase (GST), glutathione reductase (GR) and catalase (CAT) enzymatic activity, and lipid peroxidation in isolated epithelium exposed to 0.13 and 1.3 μM PST. ROS production and lysosomal membrane stability (as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…In vitro and ex vivo experiments in rainbow trout and the Patagonian silverside (Odontesthes hatcheri) suggest that microcystin-LR may act as a substrate and competitive inhibitor of ABCClike proteins in intestinal tissues (Bieczynski et al, 2014(Bieczynski et al, , 2016. Additional ex vivo and in vitro experiments in rainbow trout intestines demonstrated that paralytic shellfish toxin (PST) is capable of inhibiting ABCC-like transporters when absorbed by intestinal epithelial cells (Painefilú et al, 2020). The activity of ABC proteins can also be regulated by endogenous compounds.…”
Section: Molecular Interactions Of Xenobiotics With Mxr Transportersmentioning
confidence: 99%
“…In vitro and ex vivo experiments in rainbow trout and the Patagonian silverside (Odontesthes hatcheri) suggest that microcystin-LR may act as a substrate and competitive inhibitor of ABCClike proteins in intestinal tissues (Bieczynski et al, 2014(Bieczynski et al, , 2016. Additional ex vivo and in vitro experiments in rainbow trout intestines demonstrated that paralytic shellfish toxin (PST) is capable of inhibiting ABCC-like transporters when absorbed by intestinal epithelial cells (Painefilú et al, 2020). The activity of ABC proteins can also be regulated by endogenous compounds.…”
Section: Molecular Interactions Of Xenobiotics With Mxr Transportersmentioning
confidence: 99%
“…In fish, the studies about the ABCC protective function against toxic substances concern mostly Abcc1 and Abcc2 but also Abcc3 to 5 ( Klobučar et al, 2010 ; Cárcamo et al, 2011 ; Long et al, 2011a , b ; Bieczynski et al, 2014 , 2016 ; Painefilú et al, 2019 , 2020 ; Lu et al, 2021 ; among others). Abcc6 is involved in the regulation of tissue calcification, e.g., scales mineralization ( Parreira et al, 2018 ; Sun et al, 2021 ).…”
Section: Abc Proteinsmentioning
confidence: 99%
“…These toxins inhibit basolateral but not apical Abcc-mediated transport. However, the coexposure with the Abcc inhibitor MK571 does not increase the cytotoxic effects of PST, suggesting that these toxins are not Abcc substrates but non-competitive inhibitors ( Painefilú et al, 2020 ).…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…In the starfish Pisaster ochraceus, STXs inhibited fertilisation and decreased the ability of the starfish to attach to a substrate [60], with STXs also causing mysid mortality and larval abnormalities in sea urchins [79]. STXs have also elicited negative responses in marine fish, causing neurological symptoms and mortality in multiple species [40,42] and a range of effects on rainbow trout intestinal cells [103]. STXs have also caused altered grazing strategies and reduced reproducibility in some copepods [104,105].…”
Section: Sunstar Physiological Analysismentioning
confidence: 99%